After authoritarianism: transitional justice and democratic stability - Nalepa, Monika (Political economy of institutions and decisions, 2022)
Transitional justice – the act of reckoning with a former authoritarian regime after it has ceased to exist – has direct implications for democratic processes. Mechanisms of transitional justice have the power to influence who decides to go into politics, can shape politicians' behavior while in office, and can affect how politicians delegate policy decisions. However, these mechanisms are not all alike: some, known as transparency mechanisms, uncover authoritarian collaborators who did their work in secret while others, known as purges, fire open collaborators of the old regime. After Authoritarianism analyzes this distinction in order to uncover the contrasting effects these mechanisms have on sustaining and shaping the qualities of democratic processes. Using a highly disaggregated global transitional justice dataset, the book shows that mechanisms of transitional justice are far from being the epilogue of an outgoing authoritarian regime, and instead represent the crucial first chapter in a country's democratic story.